2022
DOI: 10.1007/s00271-022-00773-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regulated deficit irrigation on growth, yield, and berry quality of grapevines (cv. Sangiovese) grafted on rootstocks with different resistance to water deficit

Abstract: The aim of this work was to investigate the effect of full irrigation (FI), pre-veraison water deficit (RDI 1), or post-veraison water deficit (RDI 2) on growth, yield, and berry quality in container-grown, mature vines of cv. Sangiovese grafted onto either 1103P or SO4 rootstock over two consecutive growing seasons. Deficit irrigation regimes significantly affected vine water status of both rootstocks before and after veraison. Trunk diameter (TD) increment was markedly affected when water was restricted earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Yields and berry characteristics were previously published (Palai et al 2021, Caruso et al 2022 and are reported again here to allow a better appreciation of VOC results. In brief, fruit yield per vine ranged from 1.21 kg (SO4-FI in 2018) to 2.29 kg (1103P-FI in 2019) in Sangiovese, and from 1.05 kg (SO4-RDI-1 in 2019) to 2.24 kg (SO4-RDI-2) in Merlot, but no significant differences were observed between irrigation treatments and rootstocks.…”
Section: Yield and Berry Characteristicsmentioning
confidence: 79%
See 4 more Smart Citations
“…Yields and berry characteristics were previously published (Palai et al 2021, Caruso et al 2022 and are reported again here to allow a better appreciation of VOC results. In brief, fruit yield per vine ranged from 1.21 kg (SO4-FI in 2018) to 2.29 kg (1103P-FI in 2019) in Sangiovese, and from 1.05 kg (SO4-RDI-1 in 2019) to 2.24 kg (SO4-RDI-2) in Merlot, but no significant differences were observed between irrigation treatments and rootstocks.…”
Section: Yield and Berry Characteristicsmentioning
confidence: 79%
“…The different climatic conditions between the two growing seasons (especially mean air temperature) affected vine phenology and physiology (Palai et al 2021, Caruso et al 2022), as well as the total amount of glycosylated VOCs in berries (Figure S3, Tables 2,3). The crucial role of climatic conditions on glycosylated VOC profiles has been widely reported in previous studies (Bureau et al 2000, Song et al 2012, D'Onofrio et al 2018, Kovalenko et al 2021), but interestingly, results herein showed that the relationship between the different VOC classes that characterise berry aroma, and the effect of irrigation, remained consistent over both growing seasons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations